Framing Pemberitaan Maraknya Kekerasan Seksual Terhadap Remaja Putri di Media Sosial - Dina Lorensa; Gina Elisa (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
In today's digital age, numerous mass media platforms have transitioned into online formats, such as news websites, portals, and cyber media. This shift has not only altered the way the public consumes news, but also made accessing information online much more convenient compared to traditional print media. Unlike other forms of media, online platforms offer distinct advantages, including the absence of geographical restrictions, facilitating easier access to information for individuals both domestically and internationally. One prevalent issue on social media platforms is cyber sexual harassment, which has garnered increasing attention due to its escalating prevalence in cyberspace. Goldberg has noted a surge in internet users engaging in cyber sexual harassment activities on social media in recent years. The term "harassment" originates from the English equivalent "sexual harassment," as discussed earlier. Collier (1992) defines "harassment" in the Indonesian dictionary as "leceh," which denotes insults or belittlement. When coupled with the term "sexual," the concept of "harassment" pertains to gender-related behavior, normative or otherwise. The term carries connotations of negative sexual behavior that contravenes societal standards. Initially, sexual harassment was understood to occur only through physical encounters between perpetrator and victim. However, over time, it has evolved to encompass violations of norms, decency, and humanity, facilitated by technological advancements. Consequently, acts of sexual harassment can manifest in various forms, even in the absence of direct physical contact between parties.